ASA President's Task Force Statement on Statistical Significance and Replicability. Issue 4 (2nd October 2021) - Benjamini, Yoav; De Veaux, Richard D.; Efron, Bradley; Evans, Scott; Glickman, Mark; Graubard, Barry I.; He, Xuming; Meng, Xiao-Li; Reid, Nancy M.; Stigler, Stephen M.; Vardeman, Stephen B.; Wikle, Christopher K.; et al.
Abstract : The value of hypothesis testing, and the frequent misinterpretation of p-values as a cornerstone of statistical methodology, continues to be debated. In 2019, the President of the American Statistical Association (ASA) convened a Task Force to write a succinct statement about the use of statistical methods in scientific studies, specifically hypothesis tests and p-values, and their connection to replicability.